Analisis Kebutuhan Pengembangan Bahan Ajar Mata Kuliah Anatomi Tumbuhan Di Program Studi Pendidikan Biologi Universitas Mahaputra Muhammad Yamin - Darmanella Dian Eka Wati (Eduscience Development Journal, 2022)
The problem faced in learning the Plant Anatomy course is that the time allocation provided is still not sufficient to achieve the planned competency target. So we need a teaching material that can make time and learning objectives more effective. Before compiling teaching materials, lecturers need to analyze the needs for developing teaching materials. So that the teaching materials developed are in accordance with the needs of users. Based on this background, I conducted a research entitled "Analysis of the need for the development of teaching materials for the Plant Antaomi course at the Biology Education Study Program, Mahaputra Muhammad Yamin University". This study aims to determine the student's needs for the development of teaching materials for the Plant Anatomy course. The results of this study are expected to be a motivation in developing plant anatomy learning materials that are in accordance with the needs of students so that they can motivate and support the effectiveness of course learning objectives. This research belongs to the type of descriptive research. The object of this research is the class of 2021 semester 2 students as many as 14 people. The data collection technique was carried out through observation sheets and questionnaires which were analyzed descriptively. The results of the study indicate that most students need learning materials in the form of textbooks in printed, colored, and can facilitate them to be more active in learning, independent learning and can flow their creativity